Le regole alimentari religiose e i menù delle mense scolastiche: una sfida per la laicità? (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Introduzione - 2. La libertà religiosa e le regole alimentari religiose - 3. Le regole alimentari religiose e la laicità dello Stato - 4. Il menù quaresimale - 5. L’immunità dall’esposizione - 6. Conclusioni.Religious dietary rules and school lunch menus: a challenge for secularism?ABSTRACT: The paper starts from a case of dietary pluralism to discuss the possibility to justify menus sensitive to different religious dietary rules in schools’ canteens. Building on an analysis of the idea of secularism, both in its legal interpretation and in its philosophical understanding in terms of neutrality, I try to show that providing for menus sensitive to different religious dietary rules does not amount to a breach of secularism; it is, rather, a legitimate consequence of the protection of individuals’ rights to freedom of conscience and religion. Moreover, whenever institutions take action to devise and implement such menus they can be taken to act on a commitment to respecting the beliefs of minority groups in society without expecting that these groups, which are often migrant communities suffering of well-known problems of social integration, take on the burden to put forward public claims.
Keywords: Libertà religiosa e alimentazione